TXNIP contributes to induction of pro-inflammatory phenotype and caspase-3 activation in astrocytes during Alzheimer’s diseases - Junhyung Kim; Jaejoon Lim; Ik Dong Yoo; Samel Park; Jong-Seok Moon (Redox Biology, 2023)
Neuroinflammation and oxidative stress have been implicated in the pathogenesis of Alzheimer’s disease (AD). Neuroinflammation and oxidative stress are associated with neuronal death in AD. Astrocytes are linked to neuroinflammation during AD. Astrocytes are important contributors to AD progression. Although the role of thioredoxin-interacting protein (TXNIP) has been identified in inflammation and oxidative stress, the mechanism by which TXNIP regulates inflammation and oxidative stress in astrocytes during AD remains unclear. In the present study, we found that TXNIP gene levels were elevated in cerebral cortex of patients with AD. The protein levels of TXNIP were elevated in GFAP-positive astrocytes of cerebral cortex from patients with AD and APP/PS1 double-transgenic mouse model of AD. Our results showed that TXNIP increased expression of genes related to pro-inflammatory reactive astrocytes and pro-inflammatory cytokines and chemokines in human astrocytes. Moreover, TXNIP increased production of pro-inflammatory cytokines and chemokines in human astrocytes. TXNIP induced activation of NK-kB signaling and over-production of mitochondrial reactive oxygen species (mtROS) in human astrocytes. TXNIP also induced mitochondrial oxidative stress by reduction of mitochondrial respiration and ATP production in human astrocytes. Furthermore, elevated TXNIP levels are correlated with caspase-3 activation of GFAP-positive astrocytes in patients with AD and mouse AD. TXNIP induced mitochondria-dependent apoptosis via caspase-9 and caspase-3 activation in human astrocytes. These results suggest that TXNIP contributes to induction of pro-inflammatory phenotype and caspase-3 activation in astrocytes during AD.